Visual evoked potentials specific for motion onset - Kuba, M; Kubová, Z (Documenta ophthalmologica. Advances in ophthalmology, 1992)
Motion-onset visual evoked potentials were studied in 140 subjects by means of motion-onset stimulation either on a television screen or through back projecting via a moving mirror. The motion-onset visual evoked potentials were characterized in 94% of the population by a dominant negative peak with latency in the range of 135-180 ms. Motion-onset visual evoked potentials with a dominant positive peak, as described in the literature, seemed to be a variant of pattern-off visual evoked potentials, caused by the pattern-disappearance effect at the onset of motion with a high temporal frequency (the multiple of the spatial frequency of the structure and the velocity of motion) of more than 6 Hz. Such visual evoked potentials occur mainly when the stimulus is limited to the macular area only. Additionally, other stimulus and recording conditions were found to be suitable for acquiring the specific motion-onset potentials without their contamination by pattern-related components. These conditions were as follows: an aperiodic moving pattern (e.g., random dots) with a low contrast (less than 0.2); a short duration of motion (less than or equal to 200 ms) and a sufficient interstimulus interval (at least five times longer than the motion duration) to decrease the adaptation to motion; and extramacular stimulation and recording of visual evoked potentials from unipolar lateral occipital leads. Such leads should be used because of the lateralization of these visual evoked potentials (mainly to the right occipital area), which is consistent with their assumed extrastriate origin.
Keywords: rozpoznávání obrazu; Evoked Potentials, Visual; Adult; Male; zrakové evokované potenciály; vnímání pohybu; lidé; dospělí; mužské pohlaví; ženské pohlaví; Female; lidé středního věku; Humans; Motion Perception; Middle Aged; Pattern Recognition, Visual